History as metafiction: a study of three European postmodern novels, Graham Swift’s Waterland (1983), Umberto Eco’s Foucault’s Pendulum (1989), and Milan Kundera’s The Unbearable Lightness of Being (1984). - Kamol, Md. Kamrul Hassan (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in English, 2017.